Systematic Validation of a Self-Administered Questionnaire to Assess Bullying: From Elementary School to High School and by Sex - Ramos-Jimenez, Arnulfo (2018)
There is a need to develop and validate an instrument to assess school bullying in the Mexican population in order to evaluate the issue and intervene accordingly. This study validates a bullying assessment instrument named Bull-M in children from 5th to 12th grade. The Bull-M was administered to a sample size of 2,030 students from 5th to 12th grade in several schools in Ciudad Juárez, Mexico. A two-factor structure of the Bull-M was analyzed with confirmatory factor analyses across the whole sample and gender and educational levels. The confirmatory factor analyses indicate good model fits, strong factor loadings and adequate Cronbach’s alpha values to assess internal reliability of the factors and scale. The Bull-M can be used to assess bullying in students from 5th to 12th grade in northern Mexico.